CitrusKB: A comprehensive knowledge base for transcriptome and interactome of Citrus spp. infected by Xanthomonas citri subsp. citri at different infection stages - Ferrasa, Adriano; Murata, Mayara M. [UNESP]; Cofre, Teresa D. C. G. [UNESP]; Cavallini, Juliana S. [UNESP]; Peron, Gustavo [UNESP]; Julião, Maria H. M. [UNESP]; Belasque, José; Ferreira, Henrique [UNESP]; Ferro, Maria Inês T. [UNESP]; Leite, Rui P.; Penha, Helen A. [UNESP]; Carvalho, Flávia M. S. [UNESP]; et al. (Oxford University Press (OUP), 2020)
Citrus canker type A is a serious disease caused by Xanthomonas citri subsp. citri (X. citri), which is responsible for severe losses to growers and to the citrus industry worldwide. To date, no canker-resistant citrus genotypes are available, and there is limited information regarding the molecular and genetic mechanisms involved in the early stages of the citrus canker development. Here, we present the CitrusKB knowledge base. This is the first in vivo interactome database for different citrus cultivars, and it was produced to provide a valuable resource of information on citrus and their interaction with the citrus canker bacterium X. citri. CitrusKB provides tools for a user-friendly web interface to let users search and analyse a large amount of information regarding eight citrus cultivars with distinct levels of susceptibility to the disease, with controls and infected plants at different stages of infection by the citrus canker bacterium X. citri. Currently, CitrusKB comprises a reference citrus genome and its transcriptome, expressed transcripts, pseudogenes and predicted genomic variations (SNPs and SSRs). The updating process will continue over time by the incorporation of novel annotations and analysis tools. We expect that CitrusKB may substantially contribute to the field of citrus genomics. CitrusKB is accessible at http://bioinfo.deinfo.uepg.br/citrus. Users can download all the generated raw sequences and generated datasets by this study from the CitrusKB website.